2018
DOI: 10.31002/ijose.v2i2.613
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Achievement Motivation and Reading Comprehension Ability through Science Literacy to High School Students

Abstract: <p>The research is to know the relationship between achievement motivation (X1), and reading comprehension ability (X2) with science literacy ability of high school students (Y). The data is all students of class X SMA Negeri 9 Jakarta. Based on data analysis can be known coefficient correlation between X1 with Y is 0,326 correlation coefficient between X2 with Y is 0,392 and correlation coefficient between X2and X1with Y is  0,601. The motivation of pace, and the ability to read the students understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 1 publication
1
8
0
2
Order By: Relevance
“…This illustrates the ability of students to explain scientific phenomena is not classified as good criteria. Wahyuni et al, (2018), factors affecting the achievement of students' scientific literacy skills include a lack of student interest in reading and teaching materials that do not yet have scientific literacy.…”
Section: Resultsmentioning
confidence: 99%
“…This illustrates the ability of students to explain scientific phenomena is not classified as good criteria. Wahyuni et al, (2018), factors affecting the achievement of students' scientific literacy skills include a lack of student interest in reading and teaching materials that do not yet have scientific literacy.…”
Section: Resultsmentioning
confidence: 99%
“…There are some obstacle found in cycle I, one of the problems is the motivation of the student are getting unmotivated, so the teacher need give motivation to the student first due to the learning motivation are closely related to the learning outcomes (Everaert et al, 2017;Firmansyah et al, 2018;Rahmadani et al, 2017;Wahyuni et al, 2018;Wulandari & Surjono, 2013). The result showed that mobile learning is effective to improve student learning outcomes, it is following the research results of Putra et al (2017); Fatmawati (2015); Nugroho (2014); Surahman and Surjono (2017) that the use of android application-based learning media was able to improve learning outcomes.…”
Section: Cycle IImentioning
confidence: 99%
“…The learning motivation during the pandemic also decreased (Handarini & Wulandari, 2020). There is a significant relationship between learning motivation and science learning outcomes (Everaert et al, 2017;Firmansyah et al, 2018;Rahmadani et al, 2017;Wahyuni et al, 2018;Wulandari & Surjono, 2013), and this problem must be overcome by teachers. One of the strategies to improve learning outcomes by using the Smart Apps Creator 3 application.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini mengakibatkan sebagian besar siswa mendapat skor yang rendah dalam tes literasi sains. (Prakarti et al, 2018;Susiati et al, 2018;Wahyuni et al, 2018). Kemalasan membaca artikel juga diasumsikan menjadi penyebab rendahnya kemampuan berpikir kritis, sebagaimana yang diungkapkan Wakhidah (2012), bahwa jika sudah terbiasa menjadi pembaca aktif dan berdialog dengan apa yang kita baca, kita akan mengasah kemampuan berpikir kritis.…”
Section: Gambar 2 Diagram Model Regresi Linearunclassified